PENDIDIKAN KESEHATAN, DETEKSI DINI DEPRESI DAN IMPLEMENTASI SENAM OTAK UNTUK MENURUNKAN TINGKAT DEPRESI PADA LANSIA DI UPT PELAYANAN SOSIAL TRESNA WERDHA BLITAR - Dhian, Dhian Ika Priahananto (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2025)
Depression is a disruption in human function related to sad feelings and accompanying symptoms, which include changes in sleep patterns and appetite, psychomotor skills, concentration, fatigue, feelings of hopelessness and helplessness, and the desire to commit suicide. Efforts to overcome depression can be done with pharmacotherapy and psychotherapy. One psychotherapy that can be used to reduce symptoms of depression in the elderly is brain training exercises (brain gym). The movements from brain exercises will relax the brain (eliminate negative thoughts, envy, envy, etc.), stimulate coordination between the two sides of the brain (improve breathing, stamina, release tension, reduce fatigue) and help release focus barriers from the brain (improving lack of attention and concentration). Brain training activities can increase blood flow to the brain, thereby increasing the oxygen supply in the brain which can keep the organ healthy. The aim of this community service is to provide health education about depression, carry out early detection of depression and carry out brain exercises to reduce depression in the elderly. The activity steps are Health Education, early detection of depression and doing brain exercises. Results of examining the level of depression in the elderly. Of the 20 elderly before doing brain exercises, 60% experienced mild depression, 30% moderate depression and 10% severe depression. Of the 20 elderly who did brain exercises, 45% did not experience depression, 45% had mild depression, and 10% had moderate depression. So it can be concluded that after doing brain exercise the majority of elderly people do not experience depression, meaning that brain exercise can reduce the level of depression in the elderly